Advancing the Egyptian Public Broadcaster to Compete in the Digital Era - Nagy, Maha Sherif Hussein (AUC Knowledge Fountain, 2019)
In light of the dramatic technological developments the media industry is witnessing in Egypt and the region, the Egyptian public broadcaster seems missing from the scene. While many privately owned channels are offering some form of online catch-up service, the first Egyptian broadcaster is still very weak online with some presence on YouTube that does not meet the opportunities other broadcasters are benefiting from in the region as well as globally. Through a series of in-depth interviews, the study aims at closely examining the strengths and weaknesses of the current digital presence of the Egyptian public broadcaster and providing recommendations on how it can be enabled to compete with privately owned competitors. Having the legacy in the realm of linear TV in the Middle East and currently undergoing a renovation process in terms of content that is planned strongly compete within the upcoming period, a strong digital presence is a must and a key factor to succeeding in reaching such a goal. The study will identify the different formats and business models for existing competition and formulate the digital strategy that would best suit the current state of the public broadcaster.